A feasibility study on the technology transfer of unfermented pickled tomatoes - Galinato, Richie-Ann S.; Dumelod, Benelyn Domingo (1995)
During the summer months, the farmers of San Miguel, Bulacan experience a peak in tomato production, leading to large postharvest losses. It was for this reason that the development of simple but effective technology of tomato pickling was explored. Improvements made on the existing formulation and procedure for unfermented pickled tomatoes resulted to the incorporation of 26% salt level--yielding a firm product possessing a sweet-sou5r and discernible spicy flavor, having no astringent aftertaste, and with a pickling solution of medium thin consistency. When introduced to target consumers, majority liked the product and was willing to pay P20-P30 if it were available. Through as cash flow projection, it was shown that with a selling price of P20 per 8-oz bottle, a monthly net profit of about 5,800 could be assured in six month's time. Since the technology is relatively new, there is a pressing need to actualize information. Thus, a circular was created for the farmers' perusal.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Tomatoes